The teaching voice in the construction of the school curriculum (Revista Contexto & Educação, 2023)
This work seeks to analyze the process of teacher participation in the construction of the school curriculum. Based on the contributions of Giroux (1988), Apple (2006), and Sacristán (2013), who point to the centrality of teachers in the development of the school curriculum and, supported by the assumptions of qualitative research, we used semi-structured interviews with teachers of early childhood education and early years of elementary school. The information analyzed from the constructive interpretative approach expresses the predominant meanings for these professionals, who show a deficit in the valorization and promotion of spaces for dialogue, with regard to the teacher's voice in this construction of the curriculum, which limits possibilities of participation and autonomy, that justifies the importance of a work which advances in achieving greater participation by teachers in school decision-making processes.